Analysis of Moral Rights and Economic Rights of Songwriters in Cases of Unauthorized Use of Songs - Fathanudien, Anthon (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
This study aims to analyze the legal liability for violations of moral and economic rights of songwriters from the perspective of intellectual property law and civil law in Indonesia. Copyright infringements of songs—such as unauthorized use, reproduction, and omission of the songwriter’s name—still frequently occur across various social media platforms, entertainment venues, and commercial activities. This research employs a normative juridical (doctrinal) method with a statutory approach and a case approach. The data sources consist of primary legal materials (Law No. 28 of 2014 on Copyright and the Indonesian Civil Code), secondary legal materials (literature, journals, and court decisions), and tertiary legal materials. The findings indicate that song copyright infringement can be categorized as an unlawful act (onrechtmatige daad) under Article 1365 of the Indonesian Civil Code, which gives rise to obligations for compensation, cessation of infringement, and restoration of the songwriter’s reputation. In its enforcement, the Directorate General of Intellectual Property (DJKI) and Collective Management Organizations (LMK) play crucial roles in protecting economic rights and resolving disputes through mediation or civil litigation in the Commercial Court. Thus, this study affirms that intellectual property law and civil law have a synergistic relationship, both serving to provide legal protection, certainty, and justice (rechtszekerheid, gerechtigheid, en doelmatigheid) for songwriters in Indonesia.